THE IMPLEMENTATION OF PROJECT MANAGEMENT SCHEDULING USING CRITICAL PATH METHOD (CPM) AND PROJECT EVALUATION AND REVIEW TECHNIQUE (PERT) IN THE HOUSE CONSTRUCTION PROJECT IN THE MALIMIMPLEMENTATION OF PROBUKAN PERMAI III HOUSING AREAS IN NORTH MINAHASA REGENCY - Sukamta, Nuraini Retnaningrum; Jacky S B Sumarauw; Merlyn Mourah Karuntu; Magdalena Wullur; Ferdinand J Temewu; Shinta Jeanete Camelia Wangke (PT. Jurnal Center Indonesia Publisher, 2026)
Previous studies have shown that the Critical Path Method (CPM) and the Project Evaluation and Review Technique (PERT) are effective in optimizing project completion time. Based on observations, the construction of a single housing unit typically requires 64 working days. This study aims to obtain an optimal scheduling result by applying CPM and PERT to the construction project of a subsidized house type-36 in Perumahan Malimbukan Permai III, North Minahasa Regency. The analysis results indicate that the project’s critical path consists of A – B – C – D – E – F – H – K – L – M – N – P – Q. Using the CPM method, the required completion time is 55 days, while the PERT method yields an estimated 55.68 days. With a deadline of 60 days, the probability of completing the project is 99.94%. This study highlights the importance of monitoring the critical path and utilizing time estimation in project planning to prevent delays and unforeseen obstacles.